Hourly charging profiles for electric vehicles and their effect on the aggregated consumption profile in Denmark. (September 2021) - Andersen, Frits Møller; Jacobsen, Henrik Klinge; Gunkel, Philipp A.
Highlights: Charging electric vehicles at home show peak late in the evening/early night. Charging profile varies considerably between workdays/weekends, over months and places of charging. Seasonal variations are important in Denmark with May and June 35% lower than winter (Jan-March). With 25% of the fleet being electric in 2030 the aggregate peak increases between 4% and 15%. With 80% of the fleet being electric in 2040 the peak may increase between 15% and 55%. Abstract: To reduce CO2 emissions, electrification of the transport sector is a central element in many countries. For Denmark, this will considerably increase the Energy Economics and System Analysis aggregated electricity consumption. How this affects the need for production-, transmission-, and distribution capacity depends on when and where the electricity is consumed. Using hourly meter data for households having an electric vehicle and for consumption at public charge stations, the novelty of this paper is that we estimate charging profiles distinguishing between types of days, months and places of charging and conclude that charging profiles for workdays and not workdays, seasons and places of charging are significantly different. That is, evaluating effects on the power system applying an average daily charging profile is too simple. Furthermore, the actual charging behaviour is more gradual than many studies assume for a dump charging behaviour and thus less problematic for peak demand. Applying the estimated profiles, formulating alternative scenarios for the charging of electric vehicles, the effect on the aggregated hourly electricity consumption in Denmark is analysed. Main conclusions are that charging of electric vehicles increases over the evening, peaks late in the evening, contributes to increase consumption during the night and is largest during the winter. That is, electric vehicles mainly consume in off-peak periods, but with 25% of the vehicles being electric in 2030 in a most favourable scenario they contribute approx. 4% to the peak in a winter workday at 6–8 pm. In the worst case they contribute 15% to the peak. In 2040 where 80% of the vehicles are electric they contribute between 15% and 55% to the annual peak consumption in Denmark.